Variation in nutritional quality of pigmented rice varieties under different water regimes - Pennapa Jaksomsak (2020)
© 2020 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group. This study evaluated grain anthocyanin, zinc (Zn) and iron (Fe) concentrations, and grain yield of eleven purple rice varieties (PP1–PP11) grown under wetland (W+) and aerobic conditions (W0) in 2 years. There was a significant variation in the concentrations of anthocyanin, Zn and Fe, by water regime and year among the varieties with a wide range of anthocyanin (1–117 mg 100 g−1) and narrower ranges of Zn (19–41 mg kg−1) and Fe (6–19 mg kg−1) concentrations. The nutritional quality in aerobic grown rice was lower than wetland grown among the varieties with higher levels of anthocyanin (>40 mg 100 g−1), Zn (>30 mg kg−1) and Fe (>15 mg kg−1), with smaller effects of water among varieties in the lower quality ranges. The lowering of anthocyanin in aerobic grown rice was observed in the two varieties of the upland ecotype that were highest in anthocyanin concentration, as well as some wetland varieties. The grain yield (1.4–6.7 Mg ha−1) was associated negatively with grain Zn concentration (r = −0.50, P ≤ 0.001), but not with grain Fe (r = −0.14, NS0.05) or anthocyanin (r = −0.27, NS0.05). The anthocyanin concentration in the purple rice increased with Zn concentration (r = 0.57, P ≤ 0.001). Wetland condition was shown to be more favorable than aerobic culture for intense pigmentation in the production of purple rice, as well as higher Zn and Fe concentrations.